Pelatihan Media Pembelajaran Interaktif SMAN 1 Malingping - Sudrajat, Yayan; Lapasau, Merry; Hidayat, Ryan; Nurfaidzah, Aghni; Ramdani, Yusuf; Tadarus, Derry (Universitas Indraprasta PGRI, 2025)
Interactive learning media training at SMAN 1 Malingping aims to improve teacher skills in utilizing educational technology to enrich the teaching and learning process. Interactive learning media has an important role in creating interesting, effective and in-depth learning experiences, by allowing students to interact directly with teaching material. This training prioritizes the use of digital platforms and applications that can increase student motivation and participation, as well as help teachers deliver material in more varied ways. In addition, this training also provides an understanding of the importance of mastering information and communication technology (ICT) in the educational context. It is hoped that with a better understanding of interactive learning media, teachers at SMAN 1 Malingping can improve the quality of learning and support optimal student development.